GAMBAR PENETAPAN LOKASI SEBAGAI SYARAT AWAL PERMOHONAN BAGI PEMEGANG HAK UNTUK PERBUATAN PENGALIHAN TANAH DI ATAS HAK PENGELOLAAN DI KOTA BATAM - INDRA HERMAWAN (PREMISE LAW JURNAL, 2017)
Ground plan is one of the documents on allocating a plot of land in Batam, issued by BP Batam (Batam Exploitation Authority). Since there are many vested interests of its holders, its ownership can be transferred which is usually caused by buy and sell. It is found that ground plan, issued by the BP Batam is an administrative requirement in managing land; therefore, it does not guarantee its legal certainty on land ownership. It only provides physical data of the land allocated to an applicant according to the result of surveying. It is recommended that the legal domicile of the ground plan be strengthened by collaborating with the National Land Agency in order to obtain accurate data and avoid the repeated surveying. Keywords: Ground Plan, Land Rights, Land Transfer